Pengaruh Return On Asset (ROA), Return On Equity (ROE), Current Ratio (CR), Debt To Equity Ratio (DER), Dan Total Asset Turnover (TATO) Terhadap Kondisi Financial Distress (Studi Empiris Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bur - Yoyo, Toni; Agustinus Priyowidodo (LPPM Universitas Buddhi Dharma, 2024)
This study aims to examine the effect of return on assets, return on equity, current ratio, debt to equity ratio, and total asset turnover on financial distress conditions in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The independent variables used are return on asset (ROA), return on equity (ROE), current ratio (CR), debt to equity ratio (DER), and total asset turnover (TATO). The bound variable used is financial distress which is proxied by the Altman Z